POLITIK SIMBOL DAN HARMONI SOSIAL: Makna Satu Tungku Tiga Batu dalam Dinamika Politik Lokal di Fakfak Papua Barat - Saidin Ernas (DIALEKTIKA, 2018)
This paper aims to examine the political practice of symbol in the arena of local politics in Indonesia, by taking the focus on how the symbol is interpreted and used for various purposes, as a phenomenon that occurs in Fakfak (a Small town in West Papua). Based on qualitative data gathered from in-depth interviews and the results of observation field in Fakfak during the period 2012 to 20013, discovered three things that can be explained in this paper, first, the propaganda about The Furnace Three Stone as a symbol of harmony and peace in Fakfak, was accompanied the process of manipulation of symbols to various political interests of power. Second, the process of manipulating the symbols carried by mastering the control of the authority of interpretation and meaning (meaning regime) and conquered the power of civil society and local leaders to eliminate their critical reasoning. Third, this study shows that a political symbol at a certain level can create harmony and social stability, as evident from the low conflictual events in Fakfak. But socially, the politicization of the symbol will turn off the philosophical ideal values to be displayed and built through the symbol. Longer-term implications are potentially avoid appreciation and tend to gain public sympathy and antipathy deficit of meaning and the people in the future